Rightful Resistance through Public Interest Litigation in China - Junxin Jiang (Nordic Institute of Asian Studies, 2025)
This article discusses the rightful resistance in the form of public interest litigation (PIL) in China from three aspects, including broader public involvement with urbanities at the forefront, challenging the government and state-owned monopolies, and an alternative channel for rights claims and public participation. The paper argues that PIL is a rightful resistance under the authoritarian regime in which Chinese citizens are making use of the law and judicial system to fight against rights infringment and make their voices heard.